2023
DOI: 10.1371/journal.pone.0285692
|View full text |Cite
|
Sign up to set email alerts
|

Determining engineering properties of ultra-high-performance fiber-reinforced geopolymer concrete modified with different waste materials

Abstract: Reprocessing solid waste materials is a low-cost method of preserving the environment, conserving natural resources, and reducing raw material consumption. Developing ultra-high-performance concrete materials requires an immense quantity of natural raw materials. The current study seeks to tackle this issue by evaluating the effect of various discarded materials, waste glass (GW), marble waste (MW), and waste rubber powder (WRP) as a partial replacement of fine aggregates on the engineering properties of susta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 95 publications
0
9
0
Order By: Relevance
“…It was also noted that the incorporation of quartz at the proportion between 20 % and 40 % results in flowability reductions of 22 %, 28 %, and 22.5 % for the percentage of SF of 0 %, 15 %, and 30 %, respectively. Althoey et al [ 64 ] developed UHPGPC by incorporating various waste materials into its formulation. They found that the presence of WRP, GW, and MW substantially influenced the flow characteristics of UHPGPC.…”
Section: Fresh Characteristics Of Uhpgpcmentioning
confidence: 99%
See 4 more Smart Citations
“…It was also noted that the incorporation of quartz at the proportion between 20 % and 40 % results in flowability reductions of 22 %, 28 %, and 22.5 % for the percentage of SF of 0 %, 15 %, and 30 %, respectively. Althoey et al [ 64 ] developed UHPGPC by incorporating various waste materials into its formulation. They found that the presence of WRP, GW, and MW substantially influenced the flow characteristics of UHPGPC.…”
Section: Fresh Characteristics Of Uhpgpcmentioning
confidence: 99%
“…Althoey et al [ 64 ] evaluated the compressive strength of UHPGPC modified with WRP, GW, and MW. The authors noted that at GW 15 %, the most enhanced compression performance of 179 MPa was observed after 90 days of curing, compared to the control sample with a strength of 161 MPa at the same duration.…”
Section: Strength Characteristics Of Uhpgpcmentioning
confidence: 99%
See 3 more Smart Citations